N2+ lasing: Gain and absorption in the presence of rotational coherence - Lytova, Marianna; Richter, Maria; Morales, Felipe; Smirnova, Olga; Ivanov, Misha; Spanner, Michael (Physical Review A, 2020)
We simulate the pump-probe experiments of lasing in molecular nitrogen ions with particular interest in the effects of rotational wave-packet dynamics. Our computations demonstrate that the coherent preparation of rotational wave packets in N2+ by an intense short nonresonant pulse results in a modulation of the subsequent emission from B2ςu+→X2ςg+ transitions induced by a resonant seed pulse. We model the dynamics of such pumping and emission using density-matrix theory to describe the N2+ dynamics and the Maxwell wave equation to model the seed pulse propagation. We show that the gain and absorption of a delayed seed pulse is dependent on the pump-seed delay, that is, the rotational coherences excited by the pump pulse can modulate the gain and absorption of the delayed seed pulse. Further, we demonstrate that the coherent rotational dynamics of the nitrogen ions can cause lasing without electronic inversion.
CRIS-Team Scopus Importer:2023-04-20